Impactos da Educação Matemática nos currículos prescritos e praticados: estudo comparativo entre Brasil e Argentina - Oliveira, Emilio Celso de (2013)
This thesis is about the impacts in the area of Mathematics Education in curriculum prescribed and practiced in the basic education system in Brazil and Argentina. This research aims at identifying common shared aspects and specificities about Mathematics and how it is organized in both countries, as well as identifying the ways which regulate the prescribed curriculum. It also aimed at carrying on data research about Mathematics teachers assimilation towards the official curriculum orientations and also aimed at looking for clues referring to the curriculum practiced by teachers. By means of methodological procedures referred to comparative studies, the present research does a documental analysis of the National Curriculum Parameters - Parâmetros Curriculares Nacionais (PCN/Brazil) and of the Contents of the Basic Commons- Conteúdos Básicos Comuns (CBC/Argentina). It also draws a comparison of data collected in interviews by analyzing the different opinions of various professionals in Education concerning the construction of the prescribed curriculum and its implementation. As far as the results are concerned, the research presents evidence in the documents about the striking influences in the Mathematics Education relating to: the principles of curricular organization; Mathematics objectives in the curriculum; selection and organizational criteria for the contents; reference to pedagogical and methodological options; and specially conceptions about learning, problem solving, contextualization, didactic value of the History of Mathematics, the use of technology in Mathematics classes as well as recommendations about learning evaluation processes. Concerning the collected statements we can highlight the difference in teachers relation with the curricular prescriptions in both countries, bearing in mind the compulsory feature they have in Argentina and the status of orientation which is assumed in Brazil. By analyzing the interviews it was found evidence about the fact that teachers, in both countries, look for a conception about learning, present in the prescribed curriculum, in which students participate in the construction of mathematical concepts, although the impression registered is that classes are still teachers-centered. As far as the curriculum, which is used in classes, is concerned, in both countries, they are in search of incorporating the didactic orientations about context, problem-solving, the History of Mathematics and the use of technology, specially the adding machine, which prove to be impacts on Mathematics Education in the classroom